2014
DOI: 10.1098/rsbl.2013.1091
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to parasites increases promiscuity in a freshwater snail

Abstract: Under the Red Queen hypothesis, outcrossing can produce genetically variable progeny, which may be more resistant, on average, to locally adapted parasites. Mating with multiple partners may enhance this resistance by further increasing the genetic variation among offspring. We exposed Potamopyrgus antipodarum to the eggs of a sterilizing, trematode parasite and tested whether this altered mating behaviour. We found that exposure to parasites increased the number of snail mating pairs and the total number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…). These results are consistent with evidence that exposure to (Soper et al., ) and infection by Microphallus (Levri, ; Levri & Lively, ) affects P. antipodarum behaviour. In particular, infected snails forage in exposed locations (e.g., tops of rocks, vegetation surfaces) at a higher frequency than uninfected snails during the time of day when the waterfowl that are Microphallus 's final host are active, likely rendering infected snails more vulnerable to predation (Levri & Lively, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…). These results are consistent with evidence that exposure to (Soper et al., ) and infection by Microphallus (Levri, ; Levri & Lively, ) affects P. antipodarum behaviour. In particular, infected snails forage in exposed locations (e.g., tops of rocks, vegetation surfaces) at a higher frequency than uninfected snails during the time of day when the waterfowl that are Microphallus 's final host are active, likely rendering infected snails more vulnerable to predation (Levri & Lively, ).…”
Section: Discussionsupporting
confidence: 91%
“…Our inclusive analysis revealed that the majority of transcripts that are significantly differentially expressed in infected snails are downregulated relative to uninfected snails. This pattern could reflect several nonmutually exclusive phenomena, ranging from tissue/organ destruction and/or overall poor condition of infected snails (e.g., Barribeau et al., ) to reallocation of resources to genes needed for defence against and response to Microphallus infection (e.g., Ederli et al., ) to suppression and/or parasitic manipulation of P. antipodarum gene expression by Microphallus as a means of evading host immune and defence systems (e.g., Barribeau et al., ; de Bekker et al., ; Levri & Lively, ; Soper, King, Vergara, & Lively, ). It is also possible that some genes involved in resistance/susceptibility to infection were significantly differentially expressed between infected and uninfected snails prior to infection, potentially during exposure, such that the expression differences we characterize might affect whether a snail becomes infected vs. a consequence of infection per se (e.g., Keane et al., ; Knight et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…S2). These results 470 are consistent with evidence that exposure to (Soper et al 2014) and infection by Microphallus 471 (Levri & Lively 1996;Levri 1999) affects P. antipodarum behaviour. In particular, infected 472 snails forage at a higher frequency than uninfected snails during the time of day when the 473 waterfowl that are Microphallus's final host are active, rendering infected snails more vulnerable 474 to predation (Levri & Lively 1996).…”
supporting
confidence: 77%
“…A search conducted in Web of Science R Core Collection database on 10th of March 2016, produced 1000 hits when I searched for "host manipulation" AND "parasite" in "topic, " but only 66 hits when this search was combined with AND "STD * or sexual * , " and only few among these studies really reported on the manipulation of host sexual behavior by a sexually transmitted parasite ( Table 2). For example, water snails infected with a trematode increased the number of mating events and the total number of different mating partners per individual (Soper et al, 2014). Males of milkweed leaf beetle, Labidomera clivicolli, or the midge, Paratrichocladius rufiventris, enhanced mating efforts and had higher mating success when they were parasitized by mites (McLachlan, 1999;Abbot and Dill, 2001).…”
Section: Host Manipulation By Stds-rarely Evolved or Rarely Studied?mentioning
confidence: 99%
“…For example, the enhanced numbers of mating events and of different mating partners reported for a water snail infected with horizontally transmitted trematodes could be the result of a successful manipulation by a sexually transmitted parasite; however, it might also represent the outcome of an adaptation of the host, because it leads to enhanced genetic variation among the offspring and, thus, enhanced resistance to the locally adapted parasite (Soper et al, 2014). Similarly, several different mechanisms could cause the frequently reported association of elevated levels of testosterone in males with latent toxoplasmosis (Flegr et al, 2008;Shirbazou et al, 2011).…”
Section: Alternative Explanations For Phenotypic Alterations In Parasmentioning
confidence: 99%